Estimating the general exponential distribution parameters using the simulation method - النقيب, عبد الخالق عبد الجبار; كوركيس, حازم منصور; حمد, الاء ماجد (Journal of Economics and Administrative Sciences, 2010)
The main aim of this paper is to study how the different estimators of the two unknown parameters (shape and scale parameter) of a generalized exponential distribution behave for different sample sizes and for different parameter values. In particular,  . Maximum Likelihood, Percentile and Ordinary Least Square estimators had been implemented for different sample sizes (small, medium, and large) and assumed several contrasts initial values for the two parameters. Two indicators of performance Mean Square Error and Mean Percentile Error were used and the comparisons were carried out between different methods of estimation  by using monte carlo simulation technique .. It was observed from the results that the PCE method had a better performance than the other methods for different sample sizes.